Comprehension in a Scenario-Based Assessment: Domain and Topic-Specific Background Knowledge. Issue 5 (18th August 2018) - McCarthy, Kathryn S.; Guerrero, Tricia A.; Kent, Kevin M.; Allen, Laura K.; McNamara, Danielle S.; Chao, Szu-Fu; Steinberg, Jonathan; O'Reilly, Tenaha; Sabatini, John
ABSTRACT: Background knowledge is a strong predictor of reading comprehension, yet little is known about how different types of background knowledge affect comprehension. The study investigated the impacts of both domain and topic-specific background knowledge on students' ability to comprehend and learn from science texts. High school students ( n  = 3, 650) completed two background knowledge assessments, a pretest, comprehension tasks, and a posttest, in the context of the Global, Integrated, Scenario-based Assessment on ecosystems. Linear mixed-effects models revealed positive effects of background knowledge on comprehension and learning as well as an interactive effect of domain and topic-specific knowledge, such that readers with high domain knowledge but low topic-specific knowledge improved most from pretest to posttest. We discuss the potential implications of these findings for educational assessments and interventions.